Evaluación operacional de un sistema de molienda molino de bolas hardinge para mantener la eficiencia y la clasificación del mineral en la empresa Minalta S.A del cantón Zaruma , provincia de El Oro, 2014. - Salinas Yadaicela, Francisco Agustín (2015)
The objective of this research was to evaluate the operability of the ball mill type "HARDINGE" which consists of Casco, jackets or coating, Grids, grinding bodies, loading and unloading devices and drive or control the mill.